Perbandingan Virgin Coconut Oil dan Curcuma Domestica Masa Kehamilan dengan Leukhore - Ulfah, Maria; Oktaviani, Pearly Otis Putri (Jurnal Mutiara Kesehatan Masyarakat, 2022)
It is estimated that 75% of women in Indonesia have experienced vaginal discharge once in their life. This study aims to determine the ratio of virgin coconut oil and curcuma domestica to leukhore during pregnancy. This type of research is a comparative study, namely comparing Virgin Coconut Oil with Curcuma Domestica. The population in this study were pregnant women in their first trimester. This population was in the working area of ​​the Losarang Public Health Center, Indramayu Regency, from March to May as many as 116 pregnant women in their first trimester. The sample technique used was purposive sampling, the sample in this study was 44 respondents. The results of the analysis of the Mann-Whitney Test obtained data that curcuma domestica reduced significantly with a calculated F value of 8,485 and a p-value of 0.007 <0.05. So it can be concluded that the use of curcuma domestica more significantly reduces the incidence of abnormal vaginal discharge compared to the use of virgin coconut oil.